ATRT-11. MOLECULAR SUBGROUPS OF ATYPICAL TERATOID/RHABDOID TUMOR (ATRT): TOWARDS A CONSENSUS. Issue 2 (22nd June 2018) - Hasselblatt, Martin; Johann, Pascal D; Ho, Ben; Grabovska, Yura; Yao, Fupan; Bourdeaut, Franck; Frühwald, Michael C; Williamson, Dan; Kool, Marcel; Huang, Annie
Abstract: Atypical teratoid/rhabdoid tumor (ATRT) is a highly malignant brain tumor arising in young children. Inactivation of chromatin remodeling complex members SMARCB1 (INI1/hSNF5) or (rarely) SMARCA4 (Brg1) are the sole recurrent genetic alterations. Despite this apparent genetic homogeneity, several studies have independently shown that ATRT represents an epigenetically heterogeneous disease and can be divided into molecular subgroups based on gene expression and DNA methylation profiles. In an international cooperative effort, published and unpublished methylation and transcriptome data of 304 and 133 ATRTs, respectively, were compiled in order to develop a consensus on the number of molecular subgroups and their characteristics. Clustering analyses independently performed in Toronto, Heidelberg, Newcastle and Paris identified three major molecular subgroups, previously annotated as Group1/SHH/hIC2, Group2A/TYR/hIC1 and Group2B/MYC/hIC3. Concordance was high and the vast majority of ATRT was allocated to the same main molecular subgroup across different clustering approaches. Additional heterogeneity was noted within the neurogenic Group1/SHH/hIC2 subgroup, characterized by NOTCH/SHH signaling. The other two subgroups, Group2A/TYR/hIC1 and Group2B/MYC/hIC3 share activation of BMP and PDGFRB pathways, but also show subgroup-specific differences (e.g. MYC/HOX more highly expressed in Group2B/MYC/hIC3 tumors) and different anatomical associations. The majority of Group1/SHH/hIC2 and Group2B/MYC/hIC3 tumors were supratentorial, while 77% of Group2A/TYR/hIC1 tumors were located infratentorially. Of note, 7/8 spinal tumors of the dataset were allocated to Group2B/MYC/hIC3. These results represent an important step towards reaching a consensus on molecular subgrouping in ATRT, which will be pivotal for the development of subgroup-specific therapies and stratification in future clinical trials.